Holocene climatic conditions in the eastern Adriatic recorded in stalagmites from Strašna peć Cave (Croatia). (1st March 2019) - Lončar, N.; Bar-Matthews, M.; Ayalon, A.; Faivre, S.; Surić, M.
Abstract: In the study we present results of stable isotope analysis (δ 18 O, δ 13 C) of two stalagmites (SPD-1 and SPD-2) from Strašna peć Cave, situated on Dugi otok Island in the Central Adriatic region. The growth interval of the speleothems based on U-Th dating covers the period from 4.4 ka to 1.5 ka. Both speleothems show frequent δ 18 O and δ 13 C fluctuations with similar average values (δ 18 O value of -4‰ for both speleothems; and average value of δ 13 C-8.5‰ and −8.8‰, respectively). In order to reconstruct the Holocene climatic conditions in the Eastern Adriatic, the speleothem isotopic record is discussed and compared with other Holocene records. They reveal periods of drought which occurred at 4.3–4 ka and around 3.5 ka, with relatively wet phases between. From 3 ka, there is a general trend towards dryness as evidentiated by the relatively high δ 18 O values of -3.5‰ to -2.5‰ recorded in speleothem SPD-1. There is distinct trend of drying during the Roman Warm Period and further toward the Dark Age Cold Period (DACP) with shorter periods of wetter conditions. These changes coincide well with the other records, thus revealing regional events along the Eastern Adriatic.